PREVALENCE OF ANAEMIA IN MBBS MEDICAL STUDENTS AT PUMHSW UNIVERSITY NAWABSHAH. A CROSS SECTIONAL STUDY. : .JPUMHS;2024:14:03,96 102.http://doi.org/10.46536/jpumhs/2024/14.03.540 - Safdar Ali Pervez Tunio1, Naveed Sattar Shaikh2, Ghulam Mustafa Jamali3, Shefa Lakho4, Mujahid Ali Chandio5, Nimra Ameen6. (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACK GROUND: Anemia is the global health problem most frequently encountered in women, particularly young adults, and is caused by various physiological as well as lifestyle causes. OBJECTIVE: To evaluate the burden and severity of anemia among female MBBS students at People’s University of Medical and Health Sciences for Women PUMHSW Nawabshah, Pakistan. METHODS: A cross-sectional study was conducted that recruited a sample of 19 to 25-year-old female medical students. RESULTS: The mean age of subjects was 21.50 years with SD 1.65± years, the mean haemoglobin levels in non anaemic individuals was 12.58 g/dl and SD± 0.22 g/dl, in anaemic patients mean haemoglobin levels were 10.56 g/dl with SD± 1.11 g/dl. The results found a high prevalence rate of anemia among the students, with 43% of the respondents falling under the class of anemia. Most of these were mild anemia at 56%, followed by moderate 41%, and severe 3%. Contributing factors were likely poor intakes of food, irregular meal patterns, and hectic academic lives possibly influencing their nutritional status. CONCLUSION:Combating anemia among such populations would be important in the context of generating improvements in outcomes but also getting these children to perform better at school because symptoms such as fatigue and poor concentration by anemia could impact academic performance.